Tailoring crystallization phases in metallic glass nanorods via nucleus starvation - Sungwoo Sohn (Nature Portfolio, 2017)
Crystallising a bulk metallic glass usually results in separate phases. Here, the authors use metallic glass nanorods to show that as the sample size approaches the nucleation scale lengths, the crystallization behavior is dictated by the lack of nuclei and nanorods crystallise into a single phase.